Techno-economic assessment of the one-step CO2 conversion to dimethyl ether in a membrane-assisted process. (March 2023) - Poto, Serena; Vink, Thomas; Oliver, Pierre; Gallucci, Fausto; Neira d′Angelo, M. Fernanda
Abstract: This study investigates the impact of the membrane reactor (MR) technology with in-situ removal of water to boost the performance of the one-step DME synthesis via CO2 hydrogenation at process scale. Given the higher efficiency in converting the feedstock, the membrane reactor allows for a remarkable decrease in the main cost drivers of the process, i.e., the catalyst mass and the H2 feed flow, by ca. 39% and 64%, respectively. Furthermore, the MR-assisted process requires 46% less utilities than the conventional process, especially in terms of cooling water and refrigerant, with a corresponding decrease in environmental impact (i.e., 25% less CO2 emissions). Both the conventional and MR-assisted plants were found effective for the mitigation of the CO2 emissions, avoiding ca. 1.4–1.6 ton CO 2 / ton DME . However, given the higher reactor and process efficiency, the membrane technology contributes to a significant reduction (i.e., 25%) in the operating costs, which is a remarkable improvement in this OPEX intensive process. Nevertheless, the calculated minimum DME selling price (i.e., 1739 €/ton and 1960 €/ton for the MR-assisted and the conventional process, respectively) is over 3 times greater than the current DME market price. Yet, with the predicted decrease of renewable H2 price and a zero-to-negative cost for the CO2 feedstock, the MR-assisted system could become competitive with the benchmark between 2025 and 2050. Graphical Abstract: ga1 Highlights: Packed bed membrane reactor technology for the one-step CO2 conversion to DME is assessed. The PBMR allows for an increase in DME yield from 32% to 53%, with a cold gas efficiency 16% higher and 46% less utilities. Both PBMR and PBR technologies avoid about 1.5 ton of CO2 per ton of DME produced. Reduced OPEX (−22.4%) for the MR-assisted technology and similar CAPEX.